What Can We Learn from the Real Bills Doctrine? - Juha Tarkka (Credit and Capital Markets – Kredit und Kapital, 2019)
The historical development of bank liquidity doctrines is surveyed from the real bills doctrine and its antecedents to the present day. The underlying ideas of the succession of several dominant liquidity doctrines are analysed and compared, with attention to their historical contexts and respective weaknesses as exposed by experience. While the real bills doctrine is obsolete as such, its central idea that the liquidity of banks requires their credit to be linked to real income generation in the economy is unique among the different liquidity doctrines and can be useful as the liquidity regulation of banks is now subject to renewed interest. – – Der Artikel bietet einen Überblick über die historische Entwicklung von Theorien der Bankenliquidität seit der Real Bills Doktrin. Die den unterschiedlichen Liquiditätstheorien zugrundeliegenden Ideen werden analysiert und verglichen, mit besonderem Augenmerk auf ihren historischen Kontext und ihre jeweiligen Schwächen. Auch wenn die Real Bills Doktrin weitgehend überholt ist, so bleibt trotzdem ihre Kernidee, dass die Liquidität der Banken eine Koppelung der Bankkredite an die Schaffung realen Einkommens erfordert, einzigartig unter den verschiedenen Liquiditätsdoktrinen. In Zeiten eines erneuten Interesses an der Liquiditätsregulierung von Banken kann sich diese Idee als nützlich erweisen.
Keywords: B12; B26; G21; 330; Real bills; Liquidity; Bank regulation